Community Spirit and Local Wisdom: Strengthening Character Education through the Ngarot Tradition in Social Studies Learning - Jana, Jana; Hammidah, Hammidah; Chand, Ratish; Haselkorn, Jessica (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to provide an in-depth understanding of the contribution of the Ngarot tradition in shaping student character through learning Social Sciences. Methodology:This research uses a qualitative approach with a naturalistic research design. Data collection techniques used in-depth interviews and participant observation. Respondents in this study were selected based on variations in roles and involvement in the Ngarot tradition using purposive sampling techniques. Data analysis will be carried out using the Miles and Huberman model. Main Findings: The integration of Ngarot traditions in social studies learning has succeeded in improving students' character by strengthening the values of mutual cooperation and local wisdom. The impacts include increased solidarity, cooperation and environmental awareness, as well as increased appreciation of cultural heritage. School support and collaboration between teachers, students and the community played a key role in the success of this program, while the school's social environment also experienced positive improvements. The results show the effectiveness of this approach in shaping student character and enriching students' character education experiences and social knowledge. The Ngarot tradition in Indonesia has similarities with local traditions in America (Barnraising) and also Ghana (Adinkra) which have the meaning of building and strengthening a sense of togetherness, mutual cooperation and character. Novelty/Originality of this study: The uniqueness of this research lies in exploring the integration of Ngarot traditions in social studies education, enriching student character formation through deep local values.